What do students expect from teaching assistants (TAs)? Considerations of gender, race, and international status - Denise Wilson; Neha Kardam (PLoS ONE, 2025)
Teaching Assistants (TAs) make important contributions to STEM teaching in higher education. While TAs often play both peer and authority figure roles, however, relatively little is known about exactly what students expect from TAs. To fill this gap, the first major goal of this study was to comprehensively understand these expectations from a large population of undergraduate engineering students. In addition, this study sought to understand how these expectations vary with students’ gender, race/ethnicity, and international status during distinct time periods associated with the recent COVID-19 pandemic (pre-COVID, during COVID, and post COVID). Student expectations were measured via a short-answer survey question in a cross-sectional dataset at a single, large institution comprised of sophomore to senior level students ( n = 1,678) enrolled in engineering courses between 2016 and 2023. Thematic analyses were used to analyze student expectations and statistical, quantitative techniques were used to identify demographic differences. While no single majority theme emerged, many (42.9%) students thought that interactions were most important for TAs to emphasize while 37.6% believed TA preparation to be most important. A smaller but noteworthy percentage (7.61%) of students expected TAs to be caring and hospitable. Significant differences emerged in different time periods and across students’ race/ethnicity, international status, and gender. The results of this study indicate that students have a wide range of expectations of TAs and that these expectations are different for different times and classroom conditions. The results of this study can directly inform TA professional development as well as faculty guidance and supervision of TAs.